Miniaturized side-firing intracardiac photoacoustic imaging catheter for monitoring radiofrequency ablation - Shang Gao; Yang Wang; Ryo Murakami; Hiroshi Ashikaga; Young-Ho Kim; Mohammad Mehrmohammadi; Henry R. Halperin; Haichong K. Zhang (Scientific Reports)
Abstract In this paper, we introduce a miniaturized intracardiac photoacoustic (PA) imaging system based on a phased-array intracardiac echocardiography catheter. This PA imaging system enhances imaging feedback during radiofrequency (RF) ablation for atrial fibrillation (A-fib) by providing ablation-induced lesion mapping. The PA imaging catheter with a 4-mm diameter was designed, featuring flexible tip for bending and navigation through the vessels. The catheter’s imaging resolution was evaluated using a phantom study with 0.2-mm-diameter wires. In an ex vivo study, the catheter was used to detect ablation-induced necrosis in porcine cardiac tissue, evaluating its capability to image through blood layer and differentiate necrotic tissue based on spectral characteristics. The catheter achieved an imaging resolution of 647.35 ± 61.60 µm in the phantom study. In the ex vivo study, it successfully identified necrotic lesions on porcine cardiac tissue, distinguishing these from surrounding tissue based on spectral analysis. The catheter system successfully imaged through an 8-mm blood layer, effectively highlighting necrotic regions. The proposed miniaturized PA imaging catheter demonstrated high-resolution imaging capability and effective detection of ablation-induced tissue boundary. Its flexibility and small diameter allow for maneuverability through cardiac vessels, enhancing its utility for intraoperative feedback during RF ablation procedures. This advancement offers a practical tool for improving the precision and effectiveness of RF ablation in A-fib treatment by integrating high-resolution imaging and maneuverability into a PA imaging catheter, potentially facilitating its adoption in clinical practice.